Investigation of input variables on temperature rise while end milling Al/SiC metal matrix composite. (17th June 2020) - Sridhar, Srinath; Sellamani, Rajeswari
Abstract : Purpose: The purpose of this paper is to find out the optimal level as well as the influence of end mill cutter geometrical and machining parameters while machining metal matrix composite. End milling is carried out on Al 356/SiC metal matrix composites (MMC) using high-speed steel (HSS) end mill cutter. The optimum level of input parameters such as helix angle, nose radius, rake angle, cutting speed, feed rate and depth of cut are calculated for minimum temperature rise. Design/methodology/approach: L27 Taguchi orthogonal design, signal-to-noise (S/N) ratio, are applied for conducting experiments, and to find the optimal level of input parameters for minimum temperature rise, respectively. Analysis of variance (ANOVA) is used to analyze the significance of input parameters on temperature rise. Findings: It is found that the optimal combination of helix angle 400, nose radius 0.8 mm, rake angle 80, cutting speed 30 m/min, feed rate 0.04 mm/rev and depth of cut 0.5 mm have generated minimum temperature rise. From ANOVA analysis, it is found that rake angle influence is more on output performance followed by cutting speed and nose radius compared with other machining and geometrical parameters. Originality/value: The influence of geometrical parameters such as helix angle, nose radius and rake angle of end mill cutter on temperature rise while machining MMC has not been explored previously.